Room-temperature continuous-wave operation of green vertical-cavity surface-emitting lasers with a curved mirror fabricated on {20−21} semi-polar GaN. (13th March 2020) - Hamaguchi, Tatsushi; Hoshina, Yukio; Hayashi, Kentaro; Tanaka, Masayuki; Ito, Masamichi; Ohara, Maho; Jyoukawa, Tatsurou; Kobayashi, Noriko; Watanabe, Hideki; Yokozeki, Mikihiro; Koda, Rintaro; Yanashima, Katsunori
Abstract: We demonstrate a room-temperature continuous-wave operation of green vertical-cavity surface-emitting laser (VCSEL) with a 20 μ m long cavity possessing a dielectric curved mirror formed over a {20−21} semi-polar gallium nitride substrate. The emission wavelength and the threshold current were 515 nm and 1.8 mA, respectively. We also confirmed that white light is generated by overlaying three prime colors of light, i.e. red, blue and green, emitted only from VCSEL.